Medial anatomical buttress plate in treating displaced femoral neck fracture a finite element analysis. Issue 11 (November 2019) - Li, Jia; Yin, Pengbin; Zhang, Licheng; Chen, Hua; Tang, Peifu
Highlights: The FEA shows that: 1) addition of a medial buttress plate achieved superior medial buttress stability as compared to cannulated screw fixation alone, suggesting superior healing of displaced femoral neck fractures; 2) As compared to addition of 1/3TP, the application of MABP achieves superior performance because it perfectly fits with the existing anatomic structure of medial femoral neck. The FEA encouraged us that in the following biomechanical experiment, addition of a medial buttress plate not only achieved superior medial buttress stability but also achieves superior performance. Much as is the case for other FE analyses, studies using a larger cohort or randomized controlled studies including patients who require femoral neck fixation are needed in order to formally confirm our findings. Abstract: Background: Displaced femoral neck fractures in young adults are most likely to result from high energy trauma that causes a vertically-oriented shearing injury through the femoral neck. The optimal strategy for treatment of displaced femoral neck fractures remains an unsolved challenge in orthopedic surgery. Methods: our group has previously designed a medial anatomical buttress plate (MABP) based on the analysis of the computed tomography (CT) data of anatomical structures derived from a large sample population. In this study, finite element analyses (FEA) were carried out to compare the outcomes of the combination of our MABP with cannulated screws to those of the combination of tubular plate with cannulated screws, and to those of using cannulated screws alone. Results: MABP resulted in a more stable fixation as compared to the other two approaches, with respect to the femur and the stress distributions, stress peaks, and Z axis displacements. Conclusions: The FEA encouraged us that addition of a medial buttress plate not only achieved superior medial buttress stability but also achieves superior performance because it perfectly fits with the existing anatomic structure of medial femoral neck. The results from our study may provide references for clinical decision making in dealing with such patients.